Role of RuO2(100) in surface oxidation and CO oxidation catalysis on Ru(0001). Issue 1 (25th November 2015) - Flege, Jan Ingo; Lachnitt, Jan; Mazur, Daniel; Sutter, Peter; Falta, Jens
Abstract : Oxidation of Ru(0001) induces the simultaneous formation of RuO2 (100) and RuO2 (110) and a structure-sensitive oxygen spillover during CO oxidation. Abstract : We have studied the oxidation of the Ru(0001) surface by in situ microscopy during exposure to NO2, an efficient source of atomic oxygen, at elevated temperatures. In a previous investigation [Flege et al., Phys. Rev. B: Condens. Matter Mater. Phys., 2008, 78, 165407], at O coverages exceeding 1 monolayer, using the combination of intensity–voltage ( I ( V )) low-energy electron microscopy (LEEM) and multiple scattering calculations for the (00) beam in the very-low-energy range ( E ≤ 50 eV) we identified three surface components during the initial Ru oxidation: a (1 × 1)-O chemisorption phase, the RuO2 (110) oxide phase, and a surface oxide structure characterized by a trilayer O–Ru–O stacking. Here, we use dark-field LEEM imaging and micro-illumination low-energy electron diffraction in the range of 100 to 400 eV to show that this trilayer phase is actually a RuO2 (100)-(1 × 1) phase with possibly mixed O and Ru surface terminations. This identification rationalizes the thermodynamic stability of this phase at elevated temperatures and is consistent with the observation of catalytic activity of the phase in CO oxidation.